1991
DOI: 10.1093/geront/31.4.483
|View full text |Cite
|
Sign up to set email alerts
|

Finding Meaning: An Alternative Paradigm for Alzheimer's Disease Family Caregivers

Abstract: Theoretical formulations of stress and coping, family systems, crisis intervention, and loss and grief have inadequately explained how persons might grow and find meaning through their caregiving experiences. An existential theoretical framework guided the data interpretation in a qualitative study of 94 dementia family caregivers. Results suggest that an existential framework provides an alternative paradigm for understanding the caregiving experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(143 citation statements)
references
References 0 publications
8
131
0
4
Order By: Relevance
“…The research that has been conducted demonstrates that many carers cope well with the challenges they face and experience caregiving as a rewarding and satisfying experience (Cohen, Colantonio & Vernich, 2002;Farran, Keane-Hagerty, Salloway, Kupferer & Wilken, 1991).…”
Section: Positive Aspects Of Caregiving In Dementiamentioning
confidence: 99%
See 2 more Smart Citations
“…The research that has been conducted demonstrates that many carers cope well with the challenges they face and experience caregiving as a rewarding and satisfying experience (Cohen, Colantonio & Vernich, 2002;Farran, Keane-Hagerty, Salloway, Kupferer & Wilken, 1991).…”
Section: Positive Aspects Of Caregiving In Dementiamentioning
confidence: 99%
“…Firstly, the majority of the studies reported on qualitative data collected as part of larger, mixed-method studies. In some cases, opportunity or convenience sampling was used to collect the large volumes of data required for the quantitative aspects of the studies as opposed to purposive sampling preferred in qualitative methodologies (Farran, et al, 1991;Murray, Schneider, Banerjee & Mann, 1999;Narayan, Lewis, Tornatore, Hepburn & Corcoran-Perry, 2001). …”
Section: Assessment Of Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of burden thus became synonymous with caregiving in much of the scholarly and popular literature (Callahan, 1988;Montgomery, 1989). As recent studies have found, however, caregiving is fulfilling to many people, who would not give up its rewards to escape its difficulties (Farran, Keeane-Haggerty, Salloway, Kupfere, & Wilken, 1991;Given, King, Collins, & Given, 1988;Klein, 1989). Most of the participants, except a few sacrificed victims, were willing to become family caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Research in this field evolved to encompass a broader focus on psychosocial aspects such as wellbeing [35], occasionally in new ways and settings [36]. Studies combining both positive and negative aspects began to appear [37][38][39] and the complex existential dimension of caregiving came into focus through concepts such as meaning [40][41][42][43] and quality of life [36,44,45].…”
Section: Caregiving By Informal Caregiversmentioning
confidence: 99%